Giant Cell Carcinoma of Lung with Aberrant Cytoplasmic Localization of P63 Protein (Global Journal of Medical Research, 2015)
Giant Cell Carcinoma is a rare, aggressive type of lung malignancy and very few cases have been extensively studied and reported to date. Because of its rare occurrence, this neoplasm is often not included in the classifications of usual lung cancers. It is considered by some as a variant of undifferentiated large cell carcinoma. Giant cells have, however, been found to occur in different types of lung cancers and their presence in any histologic type is associated with a significantly worse outcome. We present a non-smoking female who was diagnosed with lung adenocarcinoma composed of many giant cells showing cytoplasmic expression of p63 protein. Admitting imaging studies revealed metastases to liver, lymph nodes and the pelvic region. Due to the rarity of this cancer, the diagnosis as well as therapeutic and prognostic features of giant cell carcinoma is often overlooked.
Keywords: giant cell carcinoma; aberrant p63; lung carcinoma